2017
DOI: 10.1057/s41291-017-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Inter-organizational governance and trilateral trust building: a case study of crowdsourcing-based open innovation in China

Abstract: In a case study of a Chinese crowdsourcing intermediary, we explore the impact of inter-organizational governance on trilateral trust-building. We show that formal control and relational governance mechanisms are essential for swift and knowledge-based trust in R&D crowdsourcing. The case also indicates that Chinese businesses continue to use guanxi (informal personal connections) as a relational and contingent mechanism to maintain affect-based trust, but guanxi is shown to inhibit the growth of Internet-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 78 publications
0
1
0
6
Order By: Relevance
“…Trust with a partner arises when the enterprise considers the partner to be honest. Previous research showed that trust with customers facilitates cooperation and supply chain integration (Guo et al, 2017;Wang et al, 2014). Trust with customers help to form common attitudes (Corsten and Felde, 2005) and IS (Cheng, 2011;Johnsen et al, 2019;Yeh et al, 2008).…”
Section: The Moderating Roles Of Dependence and Trustmentioning
confidence: 99%
“…Trust with a partner arises when the enterprise considers the partner to be honest. Previous research showed that trust with customers facilitates cooperation and supply chain integration (Guo et al, 2017;Wang et al, 2014). Trust with customers help to form common attitudes (Corsten and Felde, 2005) and IS (Cheng, 2011;Johnsen et al, 2019;Yeh et al, 2008).…”
Section: The Moderating Roles Of Dependence and Trustmentioning
confidence: 99%
“…De forma similar, el uso de intermediarios de concertación puede ser una estrategia más efectiva para promover la cooperación en las empresas pequeñas, que por sus características no son ampliamente reconocidas en el sistema y tienen mayor dificultad para encontrar un socio adecuado y generar lazos de confianza (Guo, Feng, McKenna y Zhang., 2017;Kivimaa, 2014). Las empresas grandes tienen por lo general mayores recursos a su disposición y son más conocidas en el entorno, rasgos que le facilitan la identificación de socios y el establecimiento de acuerdos de colaboración de forma directa.…”
Section: El Efecto Moderador Del Tamañounclassified
“…Fuente: Elaboración propia Implementar las estrategias de arriba hacia abajo, es decir desde la alta gerencia (Bervanakis & Dešić, 2013), Establecer un gobierno corporativo basado en la confianza (Guo et al, 2017).…”
Section: Ilustración 13 La Innovación Abierta Como Un Modelo Empresarialunclassified
“…La investigación básica juega un papel fundamental, por tanto, el talento humano asociado debe tener competencias blandas adecuadas para este proceso. Guo et al (2017) declara que es importante que los participantes de estas etapas evidencien sus competencias en las líneas de trabajo a abordar;…”
Section: Trl 3: Desarrollo De Concepto E Investigación Básicaunclassified
See 1 more Smart Citation